O conhecimento em ciências na educação infantil: uma abordagem teórico-metodológica - Cardoso, Michele Ferreira (2017)
The present work aims to present a didactic sequence which intends to provide knowledge in Science in Child Education structured according to the Three Pedagogical Moments from the perspective of Delizoicov and Angotti (1991). This dissertation is based on the research line of Information, Communication and Interaction Technologies applied to the teaching of Science and Mathmatics and systemaside by a sequence of activities, uses animation films, experimental activities and learning objects as pedagogical resources. It was applied in a preschool class containing nineteen children in a local public school in the town of Mormaço, RS, Brazil. The proposal relies on the Three Pedagogical Moments group dynamics and tried to insert the topic “Water Cycle” through dialogical problematization at this teaching stage. The general objective of this work is developing a didactic sequence which provides prescholar children with knowledge in Science, so as to analyze the relevance of the proposal in terms of evolution of k nowledge and interaction. In order to verify initial and final learning signs, some data collection tools were used such as audio records and their further transcripts, graphic design reports, individual interviews and a logbook. During the analysis of these instruments it was found that the activities were well explored by the class, in which a great number of students had some background knowledge, information, ideas and generalizations about the topic. The results obtained indicate that preschool childre n already explore and question about the physical and natural world spontaneously, in a process of concept learning, which makes this exploitation necessary in the school routine from the very beginning, as observed in the application of this proposal through the numerous manifestations and excitements expressed on the children’ speech. Read this dissertation an educational product in the format of a didactic sequence.